2012
DOI: 10.1038/leu.2012.151
|View full text |Cite
|
Sign up to set email alerts
|

A record-based case–control study of natural background radiation and the incidence of childhood leukaemia and other cancers in Great Britain during 1980–2006

Abstract: We conducted a large record-based case-control study testing associations between childhood cancer and natural background radiation. Cases (27 447) born and diagnosed in Great Britain during 1980–2006 and matched cancer-free controls (36 793) were from the National Registry of Childhood Tumours. Radiation exposures were estimated for mother’s residence at the child’s birth from national databases, using the County District mean for gamma-rays, and a predictive map based on domestic measurements grouped by geol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
185
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 189 publications
(202 citation statements)
references
References 30 publications
13
185
1
3
Order By: Relevance
“…Our main data source (Kendall et al, 2015) is an expanded dataset for a large record-based case-control study of naturally occurring radiation and childhood cancer in GB (Kendall et al, 2013b). This expanded dataset includes about 125,000 study subjects.…”
Section: Sources Of Informationmentioning
confidence: 99%
See 4 more Smart Citations
“…Our main data source (Kendall et al, 2015) is an expanded dataset for a large record-based case-control study of naturally occurring radiation and childhood cancer in GB (Kendall et al, 2013b). This expanded dataset includes about 125,000 study subjects.…”
Section: Sources Of Informationmentioning
confidence: 99%
“…For the data of the case-control study the investigators reported that the correlation coefficient between Carstairs Quintile and occupational social class (6 categories) was 0.28 (p<0.001) based on 57 594 study subjects (Kendall et al, 2013a).…”
Section: Measures Of Socioeconomic Statusmentioning
confidence: 99%
See 3 more Smart Citations